Women's motivation, perception and experience of complementary and alternative medicine in pregnancy: A meta-synthesis. (April 2018) - Bowman, Rebekah L.; Davis, Deborah L.; Ferguson, Sally; Taylor, Jan
Abstract: Background: complementary and Alternative Medicine use during pregnancy is popular in many countries, including Australia. There is currently little evidence to support this practice, which raises the question of women's motivation for use of these therapies and the experiences they encounter. Objective: this study aims to explore the perceptions, motivations and experiences of pregnant women with regard to their use of Complementary and Alternative Medicine during pregnancy. Methods: a systemic review and meta-synthesis of the available research was conducted. Five databases were explored – CINAHL Plus, Medline, PubMed, AMED and Web of Science using the search terms complementary and alternative medicine; pregnancy; and pregnant. Articles included in this meta-synthesis were screened using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses tool. Findings: ten initial themes were drawn from the six studies. These ten themes were summarised by three cluster themes. The results suggest that women are using Complementary and Alternative Medicine in their pregnancy as a means of supporting their sense of self-determination, to pursue a natural and safe childbirth, and because they experience a close affiliation with the philosophical underpinnings of Complementary and Alternative Medicine as an alternative to the biomedical model. Conclusion: these findings are important to practitioners, policy makers, governing bodies and researchers, providing insight into the motivations for Complementary and Alternative Medicine use by women in pregnancy. Highlights: CAM use in pregnancy is widespread. Explored themes for motivations, perceptions&experience of CAM use in pregnancy. Themes - Self-determination; pursue a natural safe childbirth; affiliation with CAM.